Mechanical difference between white and gray matter in the rat cerebellum measured by scanning force microscopy - Christ, Andreas F.; Franze, Kristian; Gautier, Helene; Moshayedi, Pouria; Fawcett, James; Franklin, Robin J. M.; Karadottir, Ragnhildur T.; Guck, Jochen (Journal of Biomechanics, 2010)
The mechanical properties of tissues are increasingly recognized as important cues for cell physiology and pathology. Nevertheless, there is a sparsity of quantitative, high-resolution data on mechanical properties of specific tissues. This is especially true for the central nervous system (CNS), which poses particular difficulties in terms of preparation and measurement. We have prepared thin slices of brain tissue suited for indentation measurements on the micrometer scale in a near-native state. Using a scanning force microscope with a spherical indenter of radius 20γm we have mapped the effective elastic modulus of rat cerebellum with a spatial resolution of 100γm. We found significant differences between white and gray matter, having effective elastic moduli of K=294±74 and 454±53Pa, respectively, at 3γm indentation depth (ng=245, nw=150 in four animals, p<0.05; errors are SD). In contrast to many other measurements on larger length scales, our results were constant for indentation depths of 2-4γm indicating a regime of linear effective elastic modulus. These data, assessed with a direct mechanical measurement, provide reliable high-resolution information and serve as a quantitative basis for further neuromechanical investigations on the mechanical properties of developing, adult and damaged CNS tissue. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Atomic force microscopy (AFM); Brain; Central nervous system (CNS); Elasticity; Stiffness